2016
DOI: 10.4172/2329-6607.1000169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucagon-Like Peptide-1 on Arteriovenous Fistula Remodelling and Vascular Smooth Muscle Cell Phenotype Switching in Diabetic Rats

Abstract: Glucagon-like peptide-1 (GLP-1) is a gut-derived hormone, belonging to the incretin family. GLP-1 is secreted by the small intestine under delicate regulation in response to blood glucose concentrations. Since GLP-1 exerts stimulatory effects on insulin release through binding to the GLP-1 receptor (GLP-1R) on pancreatic beta cells, [6,7] GLP-1 analogues have been applied clinically to control hyperglycemia AbstractThis study aimed to determine the potential vascular protective effect of exendin-4, a synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We admit that the immune diabetic models are more compatible with type II diabetes, but streptozotocin-induced insulin-dependent chronic hyperglycemia is also a valid experimental model for wound healing, particularly when the extraglycemic effect of a drug or compound is tested. 20,49 Second, the closure of excisional wounds in this study might be affected by wound contracture rather than the true effect of re-epithelialization. Nevertheless, our results clearly showed that administration of Ex4 accelerated wound closure in diabetic rats that was comparable with controls, while the diabetic wounds remained poorly healed up to 14 d after injury.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We admit that the immune diabetic models are more compatible with type II diabetes, but streptozotocin-induced insulin-dependent chronic hyperglycemia is also a valid experimental model for wound healing, particularly when the extraglycemic effect of a drug or compound is tested. 20,49 Second, the closure of excisional wounds in this study might be affected by wound contracture rather than the true effect of re-epithelialization. Nevertheless, our results clearly showed that administration of Ex4 accelerated wound closure in diabetic rats that was comparable with controls, while the diabetic wounds remained poorly healed up to 14 d after injury.…”
Section: Discussionmentioning
confidence: 92%
“…Animals were then randomly assigned to control or Ex4 treatment group and received intraperitoneal injection of normal saline or Ex4 (0.5 mg/kg/d, Sigma Aldrich) for 14 d after operation. [18][19][20] Glp-1R analogues have been widely used in the control of blood glucose levels for the past decade, and they are most commonly administered via subcutaneous injection in type II diabetic patients. Therefore, our study design followed the clinical scenario that the application of parenteral injection of Ex4 as a supplemental hypoglycemic agent in diabetic patients may provide additional effect in the promotion of wound healing.…”
Section: Rat Model Of Wound Healingmentioning
confidence: 99%